Biodegradation of halogenated organic compounds. - Chaudhry, G R (1991)
In this review we discuss the degradation of chlorinated hydrocarbons by microorganisms, emphasizing the physiological, biochemical, and genetic basis of the biodegradation of aliphatic, aromatic, and polycyclic compounds. Many environmentally important xenobiotics are halogenated, especially chlorinated. These compounds are manufactured and used as pesticides, plasticizers, paint and printing-ink components, adhesives, flame retardants, hydraulic and heat transfer fluids, refrigerants, solvents, additives for cutting oils, and textile auxiliaries. The hazardous chemicals enter the environment through production, commercial application, and waste. As a result of bioaccumulation in the food chain and groundwater contamination, they pose public health problems because many of them are toxic, mutagenic, or carcinogenic. Although synthetic chemicals are usually recalcitrant to biodegradation, microorganisms have evolved an extensive range of enzymes, pathways, and control mechanisms that are responsible for catabolism of a wide variety of such compounds. Thus, such biological degradation can be exploited to alleviate environmental pollution problems. The pathways by which a given compound is degraded are determined by the physical, chemical, and microbiological aspects of a particular environment. By understanding the genetic basis of catabolism of xenobiotics, it is possible to improve the efficacy of naturally occurring microorganisms or construct new microorganisms capable of degrading pollutants in soil and aquatic environments more efficiently. Recently a number of genes whose enzyme products have a broader substrate specificity for the degradation of aromatic compounds have been cloned and attempts have been made to construct gene cassettes or synthetic operons comprising these degradative genes. Such gene cassettes or operons can be transferred into suitable microbial hosts for extending and custom designing the pathways for rapid degradation of recalcitrant compounds. Recent developments in designing recombinant microorganisms and hybrid metabolic pathways are discussed.